A A SIMPLE OF IOT BASED SOCIAL CONTACT TRACKING FOR INFECTIOUS PATIENT USING ULTRASONIC SENSOR: A PRELIMINARY STUDY - Iful Amri; Jesi Pebralia (Prodi Fisika FST UNJA, 2022)
One of the efforts to inhibit the transmission of infectious diseases caused by viruses and bacteria is through applying physical distancing. This study aims to create a contact monitoring tool for patients who have been infected with contagious diseases based on ultrasonic sensors and the internet of things (IoT). This instrumentation system consists of four ultrasonic sensors mounted on the left, right, front and rear sides. The sensor will detect the distance of the object that is approaching directly. Then, the measurement data of each sensor will be sent to the cloud and accessed through the Blynk application. The results show that the performance of each ultrasonic sensor is excellent and can be applied as a distance measuring device between patients and other people. The calibration results show that the ultrasonic sensor can measure a distance of 10-200 cm with an R squared value of 0.999-1. In addition, the ESP8266 also shows excellent performance. ESP8266 can send data to the cloud to be accessed and displayed in the form of a bar graph on a mobile phone. Thus, the overall system can be stated that the instrumentation system has functioned and is working well.